Interaction force between magnetic field and ferromagnetic target: analytical, numerical and experimental study. (March 2019) - Neri, Paolo
In this study, an analytical model and a finite element (FE) model were developed in order to study the force produced by a permanent magnet on a ferromagnetic target. The study was aimed at estimating the magnetic action in order to design an excitation device for vibration tests. The dynamic analysis of rotating structures as compressors' bladed wheels requires a solicitation that reflects the operational conditions. If the component is made of ferromagnetic material, it is possible to use magnetic fields for the excitation. The present paper reports the interaction between planar parallel surfaces, first studied analytically and numerically, and the results were compared with experimental results. Then the interaction between sloping surfaces was analyzed, allowing an analytical boundary loss model to be developed. Finally, the FE model was improved to study the interaction between double curvature surfaces. A comparison with experimental results measured on an actual bladed wheel was performed.